THEORETICAL FOUNDATIONS FOR STUDYING REGIONAL INTEGRATION - Shaxobova Shaxzoda Avazovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. The study of regional integration has evolved beyond the universalization of the Western European model. Contemporary scholars highlight the need for comprehensive theoretical frameworks that consider historical, political, economic, and socio-cultural dimensions. This article presents a critical overview of classical and contemporary integration theories, examining their explanatory, descriptive, and prescriptive roles in understanding regional integration processes.